Maskerade (2023), volume 2 ebook - McElfresh, Andy (Maskerade (2023), 2024)
The flagship title from legendary director Kevin Smith’s Secret Stash Press is reloaded for more Masker mayhem!Maskerade continues to carve a bloody swath of vengeance through the twisted rich of Trenchen City. Volume 2 of Maskerade is finally here!Producer plaything Dwayne and Masker maker Frisky aid in Felicia’s payback plans, penetrating the antisocial circle of Trenchen’s pervy power-player elite. At the city’s rotten core lies her crafty quarry—the diabolical Dr. David Ditt! As Maskerade, she strives to strike his name off her bloody hit list and avenge her brother before Ditt and his goons perfect their own Masker—will they end Felicia once and for all?Collects Maskerade #5–#8.